Effect of Coconut Water Extract on the Growth and Serum Biochemical Values of Rats Fed Fish Oil Diet - Umar Santoso; Kazuhiro Kubo; Toru Ota; Tadahiro Tadakoro; Akio Maekawa (Indonesian Association of Food Technologists, 1998)
To justify the safety of ethanolic extract of coconut water (CWE), a study with rats was conducted. Wistar rats fedfish oil diet and rats fed the standard diei of AIN93G groupi were orally administrated 0.8 ml CWE/rat twice per day for 14 days. During experimental period, the behavior and growth of rats were monitored. At the end of experiment, the rats were anaesthetized and the internal organs were taken and measuredfor each weight. Blood was taken from the hearth and then analyzed for serum biochemical values and TBARS. The results, no adverse effects of CWE administration were observed as evaluated by growth pattern, food intake and feces appearance. Serum biochemical values and weight of internal organs of CWE receiving rats were comparable to those of untreated control. SeruniTBARS value of rats fedfish oil was significantly higher than that of those ed standard diet, however, oral administratibn of CWE did not significantly decreaie serum TBARS